PENGEMBANGAN BAHAN AJAR FISIKA BERBASIS KEARIFAN LOKAL PADA PESERTA DIDIK KELAS X DI SMAN 4 MAROS - Ramli, Ramli; Sakti, Irma; Basri, Syamsuriana; Idamyanti, Reski; Yusdarina, Yusdarina (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2024)
Development of Local Wisdom-Based Physics Teaching Materials for Grade X Students at SMAN 4 Maros. Aims to assess the validity and reliability of physics teaching materials based on local wisdom, as well as evaluate students' conceptual understanding and responses to these materials. The research and development method used is the 4-D model, which includes defining, designing, developing, and disseminating. However, dissemination was not conducted in this study due to time and budget constraints. The product was validated by media experts, subject matter experts, and physics teachers, with the research subjects being tenth-grade students at SMAN 4 Maros. The product's instrument sheets were tested for validity and reliability, and the assessment results were analyzed descriptively. Several findings indicate that the evaluation of the teaching materials showed high validity in the material aspect with a score of 3.5 (Very Valid) and a reliability of 0.947 (Very Strong), as well as in the media aspect with a score of 3.55 (Very Valid) and a reliability of 0.947 (Very Strong). The average evaluation score of the students was 13.125 (Very Good). Additionally, the questionnaire results indicated a "Very Positive" response to the physics teaching materials by 87% of the 40 participating students. Based on these assessments, the developed module is deemed highly suitable for use.